PERANAN ALI SADIKIN DALAM PEMBANGUNAN KOTA JAKARTA TAHUN 1966-77 - Widyaningrum, Paramita (Candi, 2013)
Ali Sadikin?s policy in the development of Jakarta included: political sector, economic sectors, and social cultural sector. The obstacles of Ali Sadikin faced included political, economic, and social-cultural sectors. To cope with it, Ali Sadikin conducted political establishment; took some measures oriented to expense and budget aspect, controlling and improving the local government?s financial capability based on the estimated situation faced; increased the number of school buildings and educators, illumination was held to the society about the importance of health for themselves and their environment, and he gave opportunity to the people who were capable of providing land and used former grave land. Some progress of Jakarta during the reign of Ali Sadikin included development, economic, and society moral sectors.